Anaplastic Sarcoma of the Kidney - Apostolos P. Labanaris; Vahudin Zugor; Robert Smiszek; Reinhold Nützel; Reinhard Kühn (The Scientific World Journal)
We present a case of an extremely rare and relatively new tumor entity of the kidney, the anaplastic sarcoma. Although of unknown origin and pathogenesis, treating such a tumor as if it was anaplastic Wilms' tumor seems to be the only therapeutic solution at the present time. Newer immunohistochemical staining and molecular probes should be applied to this neoplasm in order for us to understand it nature and maximize therapy.